2013
DOI: 10.3998/jmmh.10381607.0007.201
|View full text |Cite
|
Sign up to set email alerts
|

American Muslim Marital Quality: A Preliminary Investigation

Abstract: This paper describes the results of an exploratory investigation into American Muslims' marital quality. Respondents were 296 young, well-educated, long-term North American residents, most of whom lived near a major metropolitan hub. They reported generally healthy and satisfying marriages, though women reported lower marital quality than men. Marital problems most commonly included issues with in-laws, family or friends, finances, differing interests, and conflicting attitudes concerning sex. Women were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Two studies identified a 32.33% (Ba‐Yunus, ) and 21.3% (Alshugairi, ) divorce rate, but studies utilizing larger and more representative samples are needed. Research by Chapman and Cattaneo () found that 56.1% of Muslim couples reported at least one moderate or major issue in their relationship related to in‐laws, family or friends, different interests, attitudes toward sex, and finances. In another study, Macfarlane () found that changing gender‐role dynamics and mismatched expectations about family life were the most frequently reported contributors of marital conflict, along with relations with in‐laws, taking on of a second wife or infidelity, differences in religious practice, and domestic abuse.…”
Section: Muslims and Marriage Preparationmentioning
confidence: 99%
“…Two studies identified a 32.33% (Ba‐Yunus, ) and 21.3% (Alshugairi, ) divorce rate, but studies utilizing larger and more representative samples are needed. Research by Chapman and Cattaneo () found that 56.1% of Muslim couples reported at least one moderate or major issue in their relationship related to in‐laws, family or friends, different interests, attitudes toward sex, and finances. In another study, Macfarlane () found that changing gender‐role dynamics and mismatched expectations about family life were the most frequently reported contributors of marital conflict, along with relations with in‐laws, taking on of a second wife or infidelity, differences in religious practice, and domestic abuse.…”
Section: Muslims and Marriage Preparationmentioning
confidence: 99%
“…Gibbons and Hamby (1997) cautioned researchers about using instruments that are developed in western cultures, how they may not apply to nonwestern samples, and suggested adopting reliable instruments when conducting research about Muslims (Chapman & Cattaneo, 2013). Some studies tried to validate scales or questionnaires that can be used with western Muslim populations.…”
Section: Marital Instruments Utilized In Working With Muslimsmentioning
confidence: 99%
“…While there is not enough research to examine these trends, it is very apparent that Muslims value marriage and are concerned about high divorce rates. Muslim religious leaders and mental health professionals are also reporting unease with marital conflicts and dissolutions in their communities (Nadir, 1998;Siddiqui, 2009;Chapman & Cattaneo, 2013). This article examines and summarizes major research articles about Muslim marriages in the West during the past ten years (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) and provides recommendations for important research topics to be explored for the next ten years.…”
Section: The Muslim Mental Health Literaturementioning
confidence: 99%
See 1 more Smart Citation